PENERAPAN DISCOVERY LEARNING BERBANTUAN GAMBAR BERSERI UNTUK MENINGKATKAN MEMBACA PEMAHAMAN SISWA KELAS II SDN 5 PENINJOAN - Ni Kadek Sita Cahyani; Putu Beny Pradnyana; I Nengah Sueca (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the reading comprehension skills of second-grade students at SDN 5 Peninjoan in the 2025/2026 academic year through the implementation of the Discovery Learning model assisted by serial picture media. The study was motivated by students’ low ability to understand reading texts, as indicated by the number of students who had not achieved the Learning Objective Achievement Criteria (KKTP) and their tendency to read mechanically. This research employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, action implementation, observation, and reflection. The research subjects were 20 students. Data were collected through tests, observation, and documentation, and then analyzed using quantitative descriptive analysis. The results showed an improvement in students’ reading comprehension skills in each cycle. In the initial reflection stage, learning mastery reached only 20% with an average score of 63.5. In cycle II, the average score increased to 88.5 with 90% learning mastery. Therefore, the Discovery Learning model assisted by serial picture media was effective in improving students’ reading comprehension skills and can serve as an innovative learning alternative in elementary schools.